Ketone-Derived Pro-aromatic Reagents for Radical Group Transfer Reactions and Deconstructive Functionalizations - Miñoza, Shinje; Librando, Ivy L.; Liao, Hsuan-Hung (Synlett, 2023)
The recent prominence of ketones as handles for sp3-rich radicals has expanded the paradigm of synthetic utility of ketones, putting the ubiquitous functional group once again into the spotlight in recent years. One emerging strategy arose through ketone-derived pro-aromatic reagents in the form of dihydrobenzothiazoline (BTZ), dihydroquinazolinone (DHQZ), dihydropyrazole (DHP), and dihydro-1,2,4-triazole (DHT) as key intermediates for aromaticity-promoted C–C bond homolytic fission. The formed sp3-radicals could then participate in various radical functionalizations, including alkylations, arylations, olefination, alkynylation, silylations, amination, thiolation, and deuteration, among others, either in photocatalytic, thermal, or oxidative conditions. In this review, we highlight the implications and recent advances in using these pro-aromatic reagents in radical group transfer reactions and deconstructive functionalization.1 Introduction2 Aromatization-Driven C–C Bond Scission of Ketones3 Photochemical Reactions of Ketone-Derived Pro-aromatic Reagents4 Non-photochemical Reactions of Ketone-Derived Pro-aromatic Reagents5 Conclusion and Future Outlook
Keywords: aromatization; radicals; ketones; metallaphotoredox; photoredox; thermal; C–C bond activation